Empowering your church through creativity and change 30 strategies to transform your ministry - Shelley, Marshall (Nashville, TN Moorings, 1995)
Includes bibliographical references.
Keywords: Pastoral theology -- practical; Christian leadership; Change -- religious aspects -- Christianity; Creativity -- religious aspects -- Christianity